2015
DOI: 10.1111/jfpp.12536
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of E uterpe oleracea  Mart. (Açaí) and E uterpe edulis  Mart. (Juçara) Intact Fruit Using Near-Infrared (NIR) Spectroscopy and Linear Discriminant Analysis

Abstract: As the verification of authenticity of agricultural foods has become a potential application of spectroscopic methods, this study aimed to use near-infrared (NIR) spectroscopy associated with linear discriminant analysis (LDA) to discriminate intact fruit of the species Euterpe oleracea Mart. (açaí) and Euterpe edulis Mart. (juçara). One hundred sixty-eight açaí fruits from 17 genotypes and 200 fruits from 20 juçara genotypes were investigated and two groups were used for discriminating the species: calibratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…´) or purple (purple-ac ¸aı ´) colour, according to the botanical variety of the species. In contrast, the mesocarp has a thickness of 1-2 mm, is pulpy and is of variable colour, which may originate purplish pulps when originating from the purple-ac ¸aı ´or cream/greenish when coming from the white-ac ¸aı ´; the endocarp corresponds to 85-95% of the fruit, exhibiting a hard, brownish yellow seed (Dall'Acqua et al 2015;Neri-Numa et al 2018).…”
mentioning
confidence: 99%
“…´) or purple (purple-ac ¸aı ´) colour, according to the botanical variety of the species. In contrast, the mesocarp has a thickness of 1-2 mm, is pulpy and is of variable colour, which may originate purplish pulps when originating from the purple-ac ¸aı ´or cream/greenish when coming from the white-ac ¸aı ´; the endocarp corresponds to 85-95% of the fruit, exhibiting a hard, brownish yellow seed (Dall'Acqua et al 2015;Neri-Numa et al 2018).…”
mentioning
confidence: 99%
“…This discoloration may be related to anthocyanins degradation increased by this temperature, as the parameter b * since it was related to the concentration of anthocyanins on the surface of intact Açai fruit (Dall' Acqua et al . ). These values were used to determine the chroma C * and h ° attributes, indexes considered most appropriate color measurement, and are analogous to saturation or intensity (McGuire ).…”
Section: Resultsmentioning
confidence: 97%
“…The L * values were achieved on beverages from fruits blanched at 90C were lower than L * values obtained in intact Açai fruits (30.35–31.90) (Dall' Acqua et al . ), indicating that this temperature may have led to a greater darkening of the beverage. Regarding the coordinate a *, the treatment of the fruit with 150 mg/L −1 chlorination showed a lower value than the other treatments, being characterized as less red.…”
Section: Resultsmentioning
confidence: 99%
“…(Pessoa and Teixeira, 2012), with resulting impact. Due to the spectral differences of açaí and juçara populations Dall' Acqua et al (2015) reported that FT-NIR spectra pretreated with multiplicative scatter correction (MSC) had 98% correct classification and 97.3% prediction accuracy in discriminating intact açaí and juçara fruits. As a robust model should contain the maximum variation to be expressed in the prediction sets the development of a separate model may be justified (Golic and Walsh, 2006).…”
Section: Spectra and Pcamentioning
confidence: 99%